Teacher pedagogies for literacy acquisition amongst EFAL learners in Grade 3 in two schools in the Western Cape - Dooms, Anastasia Chloe (University of the Witwatersrand, Johannesburg, 2023)
The issue of literacy and language development is still a pressing concern within South African education. Many South African learners that are required to attend school and learn in their first/second additional language (FAL) as opposed to their home language (HL) are disadvantaged and comparatively excluded compared to their peers that learn in their HL. In the foundation phase, literacy acquisition is seen as a building block to education and therefore teachers need to ensure that learners have acquired adequate oral vocabulary and phonological awareness in English to enable a strong literacy foundation for their transition from their HL to English (EFAL). This study analysed the pedagogical practices used by four Grade 3 educators from two non-English schools in the Western Cape during their EFAL lessons. The research intended to identify the pedagogical approaches used by these educators to assist learners in learning and adequately acquiring their FAL to the level of proficiency needed for English as the language of instruction from Grade 4 onwards. A qualitative approach was used and incorporated the use of two EFAL lesson observations (per educator), lesson plan analyses, and semi-structured interviews. The main findings were analysed through the lens of Pedagogical Link-Making (PLM) (Scott et al., 2011). PLM as an evaluation tool was used to guide and thereafter analyse the observations and the post-observation interviews. This was used to establish the effective pedagogies used by Grade 3 educators to establish meaning amongst their learners. The findings gave insight into promising pedagogical actions that should be incorporated into teaching and learning EFAL to facilitate meaning making amongst learners and ensure adequate language and literacy acquisition. The inclusive education field will benefit from further research being conducted into PLM, with particular interest in language and literacy development. This may aid the field of education to find new ways for educators to adapt their pedagogical practices to foster inclusion within their classroom and hinder the exclusionary practices faced by EFAL learners due to learning barriers imposed by language.
This research report submitted in partial fulfilment of the requirements for the degree of Masters of Education (Inclusive Education), to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Inclusion; Pedagogical link-making; Literacy; Foundation phase; English first additional language; UCTD; SDG-4: Quality education